Subjek Hukum dan Objek Hukum: Sebuah Tinjauan Hukum Islam, Pidana dan Perdata - Witro, Doli; Rasidin, Mhd.; Nurjaman, Muhamad Izazi (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2021)
When discussing syara’ law, it is always bound by four things, namely al-Hakim, law, mahkumalaih, and mahkumfih. In various legal studies, there are various views in determining that a person can be subject to law, or in other words, capable of law. In essence, everyone is a good bearer, that is, someone who has rights and obligations. Rights bearers are also known as legal subjects. The term legal subject in the discipline of Islamic law is mentioned as mahkumalaih. If there is a legal subject, it will always go hand in hand with a legal object. In the discipline of Islamic law, the object of the law is also called mahkumfih. This article aims to discuss mahkumalaih and mahkumfih in the discipline of Islamic law. The study uses a qualitative approach that is a literature review. The materials for this article were obtained from books, journals, and internet websites related, namely mahkumalaih, and mahkumfih. The data analysis techniques used were data presentation, data reduction, and conclusion drawing. The findings showed that mahkumfih is a legal object or is interpreted as an act of mukallaf based on Allah and the Prophet’s command. In the discussion of legal objects, it cannot be separated from the legal subject. In ushulfiqh the subject of law is called mahkumalaih.